Analisis Kendala Budidaya Ikan Nila Dengan Metode Bioflok Di desa Karawana Kec. Dolo Kab. Sigi - Nova Nova; Ni Made Suwitri Parwati; Fera Fera (Transformasi: Journal of Economics and Business Management, 2023)
Efforts to increase income, provide employment, contribute to the availability of animal protein and increase production activities are part of food security in the aquaculture sector. Based on data reported from the DGT KKP Statistics, (2021) aquaculture can increase production activities, where in 2020 the third quarter of fish farming production reached 11.5 million tons and increased to 12.25 million tons in 2021 in the third quarter. Alternative techniques that can be done as an effort to increase fish farming production results are optimizing the use of biofloc system technology (Pramono et al., 2018; Faridah et al., 2019 and Permana et al., 2021). This biofloc system is a union of living organic substances into the form of blobs, where this biofloc is composed of the word bio which means life while floc means blob. For example, in tilapia farming, to increase production results so that they can ... Meeting market demand can implement a biofloc system. Tilapia is classified as a type of freshwater fish that is in great demand in the market. The advantages of implementing a biofloc system in tilapia farming are environmentally friendly so that it is easy to carry out advanced cultivation, there is efficiency in water utilization, short maintenance period, and maximizing stocking density. In addition to the advantages, there are also obstacles faced, fish farming with a biofloc system such as lack of understanding of fish farming with the biofloc method, directly providing feed without paying attention and lack of water quality control. Furthermore, the research conducted implemented the observational descriptive method.